2016
DOI: 10.1111/cea.12792
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously elevated exhaled nitric oxide and serum‐eosinophil cationic protein relate to recent asthma events in asthmatics in a cross‐sectional population‐based study

Abstract: FeNO and S-ECP are markers for inflammation in asthma, but are dependent on different inflammatory pathways and weakly correlated. Simultaneous measurements of both offer better risk characterization of adult asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…28 ECP, a protein released when eosinophils are activated, may better reflect the degree of eosinophilic inflammation in the airways and is closely related to recent exacerbations. 29,30 This may explain our result that the cases had significantly higher eosinophil counts in blood but their serum ECP only showed a statistical trend to be higher than in the controls, as their airway inflammation had not yet developed into symptomatic asthma. Measurements of ECP in sputum also showed a tendency to be higher in the cases than in the controls, which is in line with another study that showed a correlation between sputum ECP and FeNO, in children with asthma.…”
Section: Feno Represents Local Inflammation In the Airways And Relatesmentioning
confidence: 75%
“…28 ECP, a protein released when eosinophils are activated, may better reflect the degree of eosinophilic inflammation in the airways and is closely related to recent exacerbations. 29,30 This may explain our result that the cases had significantly higher eosinophil counts in blood but their serum ECP only showed a statistical trend to be higher than in the controls, as their airway inflammation had not yet developed into symptomatic asthma. Measurements of ECP in sputum also showed a tendency to be higher in the cases than in the controls, which is in line with another study that showed a correlation between sputum ECP and FeNO, in children with asthma.…”
Section: Feno Represents Local Inflammation In the Airways And Relatesmentioning
confidence: 75%
“…10 Four biomarkers known to reflect type 2 inflammation are as follows: serum periostin (S-periostin), fraction of exhaled NO (FeNO), urinary eosinophilderived neurotoxin (U-EDN), and serum eosinophil cationic protein (S-ECP). 23 It is important to identify whether there is a relation between fixed airflow obstruction and type 2 inflammation markers, as these markers of inflammation are regarded as treatable disease traits 24 and therefore might change the course of the disease. 12,13 Nitric oxide is produced by the airway epithelium and is increased by IL 4 and IL 13 in particular.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] We have previously demonstrated that a combination of type 2 biomarkers, FeNO, and S-ECP relates to more asthma attacks the preceding 3 months. 23 It is important to identify whether there is a relation between fixed airflow obstruction and type 2 inflammation markers, as these markers of inflammation are regarded as treatable disease traits 24 and therefore might change the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Mogensen et al have shown that simultaneously elevated exhaled nitric oxide and serum‐eosinophil cationic protein are related to recent asthma events in asthmatics in a cross‐sectional population‐based study. Simultaneously elevated FeNO and ECP (controlling for current smoking) were associated with more symptoms and exacerbations of asthma with each marker contributing independently to symptoms and exacerbations respectively.…”
Section: Asthma and Rhinitismentioning
confidence: 99%